Contraceptive care and method use by sexual and gender minority status: insights from a longitudinal panel of sexual and reproductive health care patients in Wisconsin - Ellie Leong; Christina E. Geddes; Fiona Weeks; Megan L. Kavanaugh (Sexual and Reproductive Health Matters)
Access to sexual and reproductive health (SRH) care is key for people to realise their reproductive goals, but sexual and gender minority (SGM) patients may experience different barriers or facilitators to access than their non-SGM counterparts. We analysed a panel dataset of 900 patients using publicly-funded SRH services in Wisconsin in 2020-2023 and constructed conditional logistic regression models to explore barriers to contraceptive services and subsequent patient-centred contraceptive method use, stratified by SGM status. Experience of barriers to wanted contraception was strongly related to preferred contraceptive use (aOR = 0.36, CI: 0.20-0.64, p = 0.002) and method satisfaction (aOR = 0.39, CI: 0.20-0.77, p = 0.010). Barriers were also linked to lower use of LARC methods by patients preferring LARC methods, including affordability barriers (aOR = 0.09, CI: 0.01-0.85, p = 0.037). SGM patients were less likely to report preferred method use (aOR = 0.18, CI: 0.08-0.42, p = 0.001) and method satisfaction (aOR = 0.30, CI: 0.11-0.81, p = 0.022) after experiencing barriers. Those who experienced affordability barriers were also less likely to report preferred method use (aOR = 0.18, CI: 0.05-0.68, p = 0.015). For non-SGM patients, only experiencing a missed healthcare visit was related to lower method satisfaction (aOR = 0.48, CI: 0.25-0.92, p = 0.029). Our study highlights that barriers to contraceptive care can hamper people’s ability to realise their contraceptive preferences. Further, our differential findings by SGM status point to potential gaps in healthcare systems that are not adequately set up to serve all patients.